Hypertriglyceridemic Waist Phenotype Predicts Increased Visceral Fat in Subjects With Type 2 Diabetes - Sam, Susan; Haffner, Steven; Davidson, Michael H.; D'Agostino, Ralph B.; Feinstein, Steven; Kondos, George; Perez, Alfonso; Mazzone, Theodore (Diabetes care, 2009)
Hypertriglyceridemic Waist Phenotype Predicts Increased Visceral Fat in Subjects With Type 2 Diabetes Susan Sam , MD 1 , Steven Haffner , MD 2 , Michael H. Davidson , MD 3 , Ralph B. D'Agostino, Sr. , MD 4 , Steven Feinstein , MD 5 , George Kondos , MD 6 , Alfonso Perez , MD 7 and Theodore Mazzone , MD 1 1 Department of Medicine, Section of Endocrinology, Diabetes and Metabolism, University of Illinois, Chicago, Illinois; 2 Department of Medicine, University of Texas Health Science Center, San Antonio, Texas; 3 Pritzker School of Medicine, University of Chicago, Chicago, Illinois; 4 Department of Mathematics, Statistics and Consulting Unit, Boston University, Boston, Massachusetts; 5 Department of Medicine, Section of Cardiology, Rush University Medical Center, Chicago, Illinois; 6 Department of Medicine, Section of Cardiology, University of Illinois College of Medicine, Chicago, Illinois; 7 Takeda Global Research and Development, Deerfield, Illinois. Corresponding author: Susan Sam, susansamatuic.edu . Abstract OBJECTIVE Greater accumulation of visceral fat is strongly linked to risk of cardiovascular disease. However, elevated waist circumference by itself does not always identify individuals with increased visceral fat. RESEARCH DESIGN AND METHODS We examined 375 subjects with type 2 diabetes from the CHICAGO cohort for presence of hypertriglyceridemic waist phenotype (waist circumference >90 cm in men or >85 cm in women, in conjunction with a plasma triglyceride concentration of ≥177 mg/dl) to determine its usefulness for identifying subjects with increased amounts of visceral fat. We divided subjects into three groups: group 1 (low waist circumference and low triglycerides; waist circumference ≤90 cm in men or ≤85 cm in women and triglyceride <177 mg/dl, n = 18), group 2 (high waist circumference and low triglycerides; waist circumference >90 cm in men or >85 cm in women and triglycerides <177 mg/dl, n = 230), and group 3 (high waist circumference and high triglycerides; waist circumference >90 cm in men or >85 cm in women and triglycerides ≥177 mg/dl, n = 127). RESULTS Subjects in group 3 had significantly higher visceral fat ( P < 0.0001), A1C ( P < 0.01), and coronary artery calcium ( P < 0.05) compared with group 2, despite similar age, BMI, and waist circumference. The relationship of the phenotype to atherosclerosis, however, was attenuated by adjustment for HDL cholesterol, triglyceride-rich lipoprotein cholesterol, apolipoprotein B, or LDL particle number. CONCLUSIONS The presence of hypertriglyceridemic waist phenotype in subjects with type 2 diabetes identifies a subset with greater degree of visceral adiposity. This subset also has greater degree of subclinical atherosclerosis that may be related to the proatherogenic lipoprotein changes. Footnotes The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked “advertisement” in accordance with 18 U.S.C. Section 1734 solely to indicate this fact. Received March 3, 2009. Accepted July 7, 2009. © 2009 by the American Diabetes Association.